Through Technological Interventions… Cucurbitaceous vegetables doubling farmers’ income - Singh, Bijendra; Pandey, Sudhakar; Singh, Mamta (Indian Horticulture, 2019)
The main goal of research on cucurbit crops in India is to double the productivity on sustainable basis. The breeding programmes were shifted towards development of biotic and abiotic resistant varieties/hybrids coupled with quality attributes. Cucurbit breeding strategy and targets are dependent on market trends. The yield potential of cucurbits could be doubled by adopting standard agro-techniques, plant-protection measures, protected cultivation and by use of grafting. Further, in order to reduce cost of hybrid seeds, it would be appropriate to utilize the available genetic mechanisms for hybrid seed production. The use of high frequency pistillate/gynoecious lines of cucumber and bitter gourd are enhancing the production of cucurbits 50-100%.